Adult Reports of Pokémon GO Play: Stronger Parasocial Relationships Predict Increased Nostalgia and Decreased App Play. (March 2020) - Frolich, Marie A.; Aguiar, Naomi Ruth; Putnam, Marisa M.; Calvert, Sandra L.
Lack of physical activity is often associated with electronic media use. However, augmented reality exergames require player movement, making them a potential health application (app). In the exergame Pokémon GO, characters were embedded into the external environment through a live camera feed and viewed through a player's smartphone screen. Online surveys from adults ( N = 230) who played the Pokémon GO app reported about their childhood emotionally tinged, parasocial relationships with a favorite Pokémon character, motivations to play Pokémon GO, and frequency of Pokémon GO play. Those who had stronger childhood parasocial relationships with a Pokémon character reported playing the Pokémon GO app for nostalgic reasons but reported less frequent app play. Older participants were motivated to play Pokémon GO to increase their physical activity levels and reported more frequent app play. The findings suggest that the age and motivations of players are important considerations for exergame design.